Virtual team work: case study of the European commission programme Erasmus Mundus Action 2. (1st January 2014) - Sadecka, Anna
The European Commission programme Erasmus Mundus Action 2 provides support for cooperation partnerships between European and Third Country higher education institutions. The purpose of this paper is to present how these partnerships operate as virtual teams and what common challenges they face. The study described in this paper was conducted among coordinators of 47 Erasmus Mundus Action 2 projects for different geographical regions. It consists of a short survey and semi–structured interviews. The results prove that Erasmus Mundus Action 2 virtual teams are able to work efficiently across geographical areas, time zones, organisational structures and cultures. They encounter similar challenges connected with virtual communication, including: adherence to the communication plan and code of conduct by all the partners, equal participation, misunderstandings and misinterpretations, technical problems. Further educational programmes, such as Erasmus+, are likely to result in a great number of innovative projects that will be developed by multinational virtual teams.